1986
DOI: 10.1111/j.1365-2559.1986.tb02510.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver disease in pregnancy

Abstract: The diseases which affect the liver in pregnancy can be subdivided into those which occur simultaneously with gestation and those which occur in the context of and exclusively during pregnancy. This review deals with the latter group and describes the histopathological features of acute fatty liver of pregnancy and liver disease in toxaemia of pregnancy, hyperemesis gravidarum and intrahepatic cholestasis of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 59 publications
0
59
0
2
Order By: Relevance
“…Liver biopsy is rarely necessary for diagnosis. Histology is characterized by cholestasis without inflammation, and bile plugs in hepatocytes and canaliculi predominate in zone 3 [58] .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Liver biopsy is rarely necessary for diagnosis. Histology is characterized by cholestasis without inflammation, and bile plugs in hepatocytes and canaliculi predominate in zone 3 [58] .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In vitamin K deficiency, the coagulation factor's protein (antigen) will be normal for age but the functional activity will be reduced [6], Current evidence suggests that the liver is not involved in the etiology of preeclampsia, but is rather a target organ for pathological change [3], Weiner and Keller [7] reported that antithrombin III activity and fibrinopeptide A concentrations were not different between control and cord blood from pre eclamptic gestations. Their study suggested that the fetal clotting cascade was not acti vated by maternal preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in liver enzymes and hepatic synthesized clotting factors are well documented [1][2][3]. Changes in cord blood clotting factors of newborns of preeclamptic mothers have also been re ported [4].…”
mentioning
confidence: 99%
“…Histopathology is characterized by pure cholestasis, sometimes with bile plugs in the hepatocytes and canaliculi, predominantly in zone 3. Inflammation and necrosis are not usually observed, and the portal tracts are unaffected [20].…”
Section: Pathologymentioning
confidence: 99%